Urban Floating Farming: The Alternative of Valuable Private Green Space for Urban Communities in the Wetland Area - Dienny Redha Rahmani; Wahyunah Wayhunah (ESE International Journal (Environmental Science and Engineering), 2019)
Green Space is a real problem at urban wetland area. Furthermore, adding it without economic value makes people not interested because it is considered to only consume land, time, energy and of course costs. Therefore, it is necessary to study related to the use of wetlands as private green spaces that are economically valuable. On the other hand, agriculture in wetlands has technology derived from local wisdom, namely floating agriculture. Therefore, it is necessary to study the adaptation of floating agriculture on a smaller scale at the level of urban settlements. This research was conducted by creating a miniature model of floating agriculture that can be applied on a private green space scale. the plant used is Celery (Apium graveolens), because This plant was chosen because celery is a wetland vegetable so it is assumed celery can represent the growth of an effective type of vegetable farming in a wetland. Growth measurements were carried out on average growth quality. The test results show that the Urban Floating Farming model can potentially be used as an alternative to green open space for urban communities.